SPECIAL ISSUE ON CONTEMPORARY PERSPECTIVES IN SCIENCE, TECHNOLOGY, HUMANITIES AND MANAGEMENT - Bouras, Haron; Arul, R; T S, Sujith; Sridharan, Manikandan; Porwal, Rajesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The ShodhKosh: Journal of Visual and Performing Arts invites original research papers, review articles, and scholarly contributions for a Special Issue titled “Contemporary Perspectives in Science, Technology, Humanities and Management.” This issue aims to promote interdisciplinary dialogue on emerging developments across scientific innovation, digital transformation, humanistic inquiry, cultural studies, organizational practices, and sustainable management. It welcomes theoretical, empirical, conceptual, and practice-based studies that examine contemporary challenges through integrated perspectives. Contributors are encouraged to explore technology, education, leadership, communication, entrepreneurship, ethics, sustainability, and human-centered development. The editorial team invites meaningful submissions that enrich current academic and professional discourse. Dr. Haron Bouras Département du langue Française, Faculté des Lettres et des Langues, Université de Souk Ahras, Souk Ahras , 41000. Algérie Email: haron.bouras@univ-soukahras.dz Dr. R Arul Assistant Professor, Department of Commerce, St.Joseph's College (Autonomous), Tiruchirappalli, India Email: arulfriends2005@gmail.com Dr. Sujith T S Assistant Professor, Department of Commerce and Management, School of Arts, Humanities and Commerce, Amrita Vishwa Vidyapeetham, Kochi Campus, Kerala, India Email: sujiththelapurath@gmail.com Dr. Manikandan Sridharan Dean (Technical Affairs, Research and Branding) and Associate Professor of Information Technology in E.G.S. Pillay Engineering College (Autonomous), Nagapattinam, Tamil Nadu, India Email: profmaninvp@gmail.com Dr. Rajesh Kumar Porwal Professor & Dean, Faculty of Mechanical Engineering, Shri Ramswaroop Memorial University, Barabanki, Uttar Pradesh, India Email: porwal.rajesh@gmail.com